2013
DOI: 10.1177/193229681300700531
|View full text |Cite
|
Sign up to set email alerts
|

A New Test Strip Technology Platform for Self-Monitoring of Blood Glucose

Abstract: In the management of diabetes, accuracy of devices used for self-monitoring of blood glucose (SMBG) is critical because SMBG results can affect patient diabetes-related health outcomes. A new blood glucose monitoring system (BGMS) platform has been developed that is based on the new CONTOUR ® NEXT (CN) test strip. This BGMS platform uses a proprietary electron mediator and algorithm to minimize errors at different steps in the testing process, thus minimizing outliers and significantly improving accuracy from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…It has been demonstrated that this BGMS fulfills the standards as laid out in ISO 15197 section 6.3, including the more stringent requirements introduced in 2013. 6,7,18 Noteworthy comparative studies reported good performance of CXT-BGMS when ISO 15197:2013 accuracy limits were applied. 16,17,19 In a recent multicenter study conducted in 21 hospitals under routine conditions using 2100 leftover blood samples, 20 CXT-BGMS results were remarkably congruent with the present data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that this BGMS fulfills the standards as laid out in ISO 15197 section 6.3, including the more stringent requirements introduced in 2013. 6,7,18 Noteworthy comparative studies reported good performance of CXT-BGMS when ISO 15197:2013 accuracy limits were applied. 16,17,19 In a recent multicenter study conducted in 21 hospitals under routine conditions using 2100 leftover blood samples, 20 CXT-BGMS results were remarkably congruent with the present data.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were exclusively collected in tubes containing lithium heparin. Samples with hematocrit results outside the CXT-BGMS range (>70%) 7 were considered nonevaluable. Blood glucose levels were measured using the CXT-BGMS, and the local, available hexokinase method (Dimension® Vista 1500, Siemens AG, Erlangen.…”
Section: Methodsmentioning
confidence: 99%
“…System accuracy and other performance data of the systems investigated have also been reported in other studies. [9][10][11][12][13][14][15][16][17][18][19] However, in our study, each system was evaluated by using 2 established comparison methods/systems, a GOD-based method/YSI 2300 STAT Plus glucose analyzer and a HK-based method/cobas c111 analyzer; the use of 2 methods allows for an investigation of possible impacts of the used comparison method/system on system accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Xylose has on the other hand been identified as a potential interfering substance in blood glucose meters employing glucose-dehydrogenase based strip technologies. 10,11 According to our knowledge, the extent of this effect has not been explored in a comparative investigation yet.…”
Section: 20mentioning
confidence: 99%
“…This situation has to be considered, when selecting blood glucose meters for patient self-testing of blood glucose, as blood glucose strip technologies based on glucosidehydrogenase have been identified to be subject to interference by xylose. 10,11 No or only very limited data exist about the real potential risk for wrong readings for patients consuming xylose containing food. It may be useful to quantify the influence of xylose on glucose meter readings to be able to define educational needs, if applicable.…”
mentioning
confidence: 99%